Exact algorithms for incremental deployment of hydrogen refuelling stations. (13th August 2021) - Kim, Hyunjoon; Kim, Byung-In; Thiel, Daniel
Abstract: Given the large investments required to establish hydrogen refuelling stations (HRSs) and the difficulty in forecasting the sales of fuel cell electric vehicles, incremental HRS deployment offers an efficient method of establishing hydrogen infrastructure with a sufficient load factor and low financial risk. Considering that some HRSs are already in use, this study assumed that the optimal location of a new HRS maximises its distance from existing HRSs and minimises its distance from customer demand points. Accordingly, a multi-objective location model and efficient exact solution methods were proposed to determine the optimal location of one or two new HRSs. As a case study, the solution methods were applied to supply hydrogen to an increasing captive fleet of taxis in a large metropolis such as Paris with fixed demand points. The methods can be widely applied to effectively install one or two HRSs incrementally. Highlights: The incremental hydrogen refuelling station (HRS) deployment problem is addressed. A multi-objective location model is proposed. An efficient exact solution approach for incremental HRS deployment is proposed. The proposed algorithm can find Pareto optimal solutions quickly. A large city with a captive fuel cell taxi fleet is used as a case study.